PENGARUH INTELLECTUAL CAPITAL, KEPEMILIKAN ASING, DAN STRUKTUR MODAL TERHADAP PROFITABILITAS - Syiva Widichesty; Abubakar Arief (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2021)
At this time, as desired by stakeholders, the company's profitability is not only influenced by financial performance, but also other non-financial performance which can be measured through intellectual capital. Thus study aims to analyze the effect of intellectual capital, foreign ownership, and capital structure on profitability. In this study, capital structure was measured in debt to equity ratio (DER) and profitability as a return on assets (ROA). The study used a sample of non-financial services companies listed in the Indonesian Stock Exchange for 2015-2019. Data samples were determined by using a purposive sampling method. The study conduct 95 observation of 19 samples of the companies. The type of data used is the secondary data with the analysis technique using the regression data panel on eviews 9. The result showed partially that intellectual capital has a significant positive effect on ROA, while foreign ownership has a significant negative effect on Profitability but capital structure has no effect on profitability.